Bio-efficacy of new herbicides on weed dynamics, productivity and nutrient uptake in maize (Zea mays) under rainfed condition of Jhabua hills - YADAV, RAKESH KUMAR; KUMAWAT, NARENDRA; SINGH, A; TOMAR, I S; SINGH, MAHENDER; MORYA, JAGDEESH; KUMAR, RAKESH; UPADHYAY, PRAVIN KUMAR (The Indian Journal of Agricultural Sciences, 2018)
Field studies were conducted during the rainy seasons of 2014 and 2015 at Zonal Agricultural Research Station, Jhabua under the rainfed condition to determine the effect of new herbicides on weed dynamic, yield and nutrient uptake in maize (Zea mays L.). Results revealed that application of saflufenacil 68 g/l + diamethanamid-P 600 g/l EC (85 +750 g/ha) recorded the lowest weed density of sedges, grasses and broad leaf weeds in maize, and improved growth, yield attributes and yield of maize. The highest grain yield (3.37 t/ha), stover yield (4.17 t/ha) and biological yield (7.57 t/ha) was recorded with saflufenacil 68 g/l+diamethanamid-P 600 g/l EC (85 +750 g/ha). This treatment also recorded the higher NPK content (1.53, 0.24, 0.34% and 1.01, 0.13, 1.36%, respectively) and uptake (52.06, 8.13, 11.40 kg/ha and 42.08, 5.46, 56.66 kg/ha, respectively) by grain as well as stover. The maximum gross returns (Rupees 52 525/ha), net returns (Rupees 36 125/ha), B: C ratio (2.20), production efficiency (26.98 kg/ha/day) and economic efficiency (Rupees 286.70/ha/day) were recorded under saflufenacil 68 g/l+diamethanamid-P 600 g/l EC (85 +750 g/ha). Hence, for better control of weeds, higher productivity and profitability of maize, herbicide mixture, i.e. saflufenacil 68 g/l + diamethanamid-P 600 g/l EC (85 +750 g/ha) should be applied as pre-emergence under rainfed condition of Jhabua hills of Madhya Pradesh.